Distributional range expansion of Cataractocoris Marginiventris Usinger (Hemiptera: Heteroptera: Naucoridae) and first record from El Salvador - Herrera, Federico (2016)
The presence of the species Cataractocoris marginiventris is recorded for the first time in El Salvador, which represents a significant expansion of the species' distribution range towards the south.